On estimation of rate of convergence in multidimensional integral theorem in the case of stable symmetric limit law - Banys, J. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. И. Банис. Оценка скорости сходимости в многомерной интегральной предельной теореме в случае сходимости к устойчивому симметрическому законуJ. Banys. Konvergavimo greičio įvertinimas daugiamatėje integralinėje teoremoje stabilaus simetrinio ribinio dėsnio atveju